Evaluating Understanding and Perceptions Towards ADHD Among Early Childhood Teachers in Karara Block, Assam (International Journal of Physiotherapy, 2025)
Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental condition marked by persistent patterns of inattention, hyperactivity, and impulsivity. Symptoms usually appear before the age of 12 and can severely disrupt functioning in various areas, such as education, work, and social interactions. In India, the understanding and awareness of Attention Deficit Hyperactivity Disorder (ADHD) are still evolving. Recent research reveals that a considerable segment of the population lacks knowledge about this disorder, despite its widespread occurrence. Studies indicate that the prevalence of adult ADHD in India varies between 5.48% and 25.7%, signifying a notable number of individuals impacted by this condition.Methods: The study employed a cross-sectional survey, recruiting a convenience sample of 50 lower primary school teachers from schools in the Karara Block of Assam. The participants were teachers currently teaching classes 1 to 5. The participation of teachers in the research was contingent upon their informed consent and compliance with the defined inclusion criteria. A comprehensive questionnaire was developed to assess teachers' knowledge of Attention Deficit Hyperactivity Disorder (ADHD). It is organized into three main sections. The first section, Demographic Information, the second section, Knowledge of ADHD, and the final section, Management Strategies. Descriptive statistics and chisquare test thoroughly analyzed the data.Results: The results of the study revealed a limited understanding of Attention-Deficit/Hyperactivity Disorder (ADHD) among the participating teachers, and only 40% correctly recognized 'difficulty following instructions' as a symptom of inattention. A significant 75% of the teachers showed a lack of knowledge regarding the recognized diagnostic criteria for ADHD. The study employed chi-square tests, and the findings revealed a statistically significant correlation, demonstrating that prior training on ADHD was associated with greater knowledge of its symptoms (χ²(1) = 6.84, p < 0.01).Conclusion: The study results highlight the need for comprehensive training initiatives aimed at enhancing teachers' understanding of Attention Deficit Hyperactivity Disorder (ADHD). The goal is to equip teachers with the necessary skills to identify and assist students with ADHD in educational settings.